Cervical dystonia and no oculomotor apraxia as new manifestation of ataxia-telangiectasia-like disorder 1 – case report and review of the literature - Bajek, Agnieszka; Przewodowska, Dominika; Koziorowski, Dariusz; Jędrzejowska, Maria; Szlufik, Stanisław (Frontiers in Neurology, 2023)
Ataxia-telangiectasia-like disorder 1 (ATLD1) is a rare neurodegenerative disorder associated with early onset ataxia and oculomotor apraxia. The genetic determination of ATLD1 is a mutation in the MRE11 gene (meiotic recombination 11 gene), which causes DNA-double strand break repair deficits. Clinical features of patients with ATLD1 resemble those of ataxia telangiectasia (AT), with slower progression and milder presentation. Main symptoms include progressive cerebellar ataxia, oculomotor apraxia, cellular hypersensitivity to ionizing radiations. Facial dyskinesia, dystonia, dysarthria have also been reported. Here we present a 45-year old woman with cervical and facial dystonia, dysarthria and ataxia, who turned out to be the first case of ATLD without oculomotor apraxia, and with dystonia as a main manifestation of the disease. She had presented those non-specific symptoms for years, before whole exome sequencing confirmed the diagnosis.